Bistatic configurational analysis of ultra-wideband antenna for detection applications - Jawab Ali; Noorsaliza Abdullah; Roshayati Yahya; Ezri Mohd; Ariffuddin Joret; Norshidah Katiran (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
With the advancement in technology, antennae are becoming a popular components to be used in various applications. Following the trend, a compact design of ultra-wideband (UWB) bistatic configuration of the antenna is presented in this paper using ground penetrating radar (GPR) technology specifically for detection applications. The antenna is first designed and simulated using defected ground structure (DGS) for impedance bandwidth with the obtained gain of around 6.2 dB and return losses from 3-16 GHz. Later the complete detection model is aimed to study and for this purpose CST is used to model human skin and performed an experiment based on antennas i.e. transmitter and receiver, obstacle and target, to study and analyze the received antenna reflections for detection purpose.